Reliability analysis of gas pipelines under global bending and thermal loadings considering a high chloride ion environment - Li, Yitao (2024)
The long-distance gas pipelines inevitably experience global bending deformation due to the ground movements. Meanwhile, a harsh environment where both the temperature may change drastically and the high chloride ion soil condition possibly causes more severe corrosion on the pipelines, could pose a significant challenge to pipeline safety. It is very crucial to ensure gas pipeline safety and durability in the energy transportation industry. Therefore, this study aims to systematically investigate the failure pressure of corroded gas pipelines under the combined effects of global bending and temperature difference. Considering gas pipelines potentially exposed to soil conditions with different contents of sodium chloride (NaCl), five corrosion rate models were for the first time employed to carry out reliability-based lifetime prediction analysis. The results show that compared to the case without global bending and temperature difference, the service life of gas pipelines can be reduced by 14 % in the case of global bending strain of 0.25 % and temperature difference of −40 °C. As for the corrosion rate model, the Model 4 plays a strongly adverse role in the service life of gas pipelines. Furthermore, parametric sensitivity analysis indicates that apart from the working pressure, initial corrosion depth and the radial corrosion rate are the two more influential factors in affecting the service life of gas pipelines.